Structural control on the initiation and development of the Biała Wisełka Landslide Complex (Silesian Beskid, Outer Carpathians, Southern Poland) - Sikora, Rafał (Geology, Geophysics and Environment, 2018)
The numerous landslides which have developed in the mostly Cretaceous to Eocene turbiditic rocks of the Silesian Beskid are genetically and geometrically controlled by bedrock structural features, the Biała Wisełka Landslide Complex being no exception. Its location is in the headwater area of the Wisła River, on the slopes of Mt. Barania Góra (1220 m a.s.l.). The bedrock is represented by flysch strata of the Silesian Nappe (Outer Carpathian Fold-and-Thrust Belt), or, more specifically, the Upper Cretaceous turbiditic Upper Godula and Lower Istebna Beds of the Godula Thrust Sheet. The research work consisted in their mapping and structural analysis, facilitated by the use of a high-resolution digital elevation model based on LiDAR data. A comparative analysis enabled the determination of the relationships between landslides and the bedrock structure. The study results point to significant roles being played by the joint network, fault systems, the structural arrangement and the lithology of rock strata in the initiation and evolution of the studied landslide complex. An additional result of the methods applied methods was the identification and characterization of previously unknown fault zones in the study area.